Analysis of different geometrical features to achieve close-to-bone stiffness material properties in medical device: A feasibility numerical study. (June 2022) - Mirulla, Agostino Igor; Muccioli, Giulio Maria Marcheggiani; Fratini, Stefano; Zaffagnini, Stefano; Ingrassia, Tommaso; Bragonzoni, Laura; Innocenti, Bernardo
Highlights: The greater material stiffness reduction could be achieved implementing internal body gaps with hexagonal or circular transversal section. A stiffness reduction up to 12% has been achieved in Young Modulus in cube with prismatic gaps realized through circular transversal section. Internal gaps distributed in 4 mm of thickness could be quite enough to obtain stiffness reduction. Abstract: Background and objective: In orthopedic medical devices, elasto-plastic behavior differences between bone and metallic materials could lead to mechanical issues at the bone-implant interface, as stress shielding. Those issue are mainly related to knee and hip arthroplasty, and they could be responsible for implant failure. To reduce mismatching-related adverse events between bone and prosthesis mechanical properties, modifying the implant's internal geometry varying the bulk stiffness and density could be the right approach. Therefore, this feasibility study aims to assess which in-body gap geometry improves, by reducing, the bulk stiffness. Methods: Using five finite element models, a uniaxial compression test in five cubes with a 20 mm thickness was simulated and analyzed. The displacements, strain and Young Modulus were calculated in four cubes, each containing internal prismatic gaps with different transversal sections (squared, hexagonal, octagonal, and circular). Those were compared with a fifth full-volume cube used as control. Results: The most significant difference have been achieved in displacement values, in cubes containing internal gaps with hexagonal and circular transversal sections (82 µm and 82.5 µm, respectively), when compared to the full-volume cube (69.3 µm). Conclusions: This study suggests that hexagonal and circular shape of the gaps allows obtaining the lower rigidity in a size range of 4 mm, offering a starting approach to achieve a "close-to-bone" material, with a potential use in prosthetic devices with limited thickness.